Contributions to the knowledge and distribution of Pucciniales (rust fungi) in three Brazilian biomes - Martins Junior, Alcindo Da Silva; Gomes, Paulo Weslem Portal; Sakuragui, Cássia Mônica; Carvalho Junior, Aníbal Alves De (Phytotaxa, 2022)
Inventories of Pucciniales in areas of Cerrado, Atlantic Forest and the Amazon forest were carried out to fill the knowledge gap about this order and update the hosts and geographic distribution of the recorded species. After the analysis of 424 samples of plants infected with Pucciniales, we identified 122 species distributed in 37 (anamorphic and teleomorphic) genera parasitizing host plants of 101 genera of 43 botanical families. This study is the first to present results of inventories at national level and gathers information about 15% of the total number of Pucciniales registered in Brazil. The Atlantic Forest had the largest number of species of Pucciniales (63), followed by Cerrado (60) and the Amazon forest (31). The three biomes showed unique mycobiotas. We present new occurrences of species for Brazil, for the regions of the Amazon Forest, Cerrado and Atlantic Forest, and for the local areas studied. The results also increase the number of hosts of previously registered rust fungi.